effects of - KOTHARI, SOMYA (2017)
The present research aimed at the examination of the impacts of Globalisation on the firm strategies and performance of the UK IT industry. In today’s market place which is globalised to a great extent, the ways of successfully leveraging opportunities lie within the context of globalisation wherein IT convergence might necessitate the IT organisations to emphasize more on the global challenges and opportunities. The adoption of business is high in the UK IT industry and the businesses that are conducted in the top of the world UK scenario hinge towards the use of internet and customer interaction and with the production network. Hence it is imperative to examine whether globalisation tends to have effects on firm performance in the UK IT industry. The research adopted survey based methodology to collect primary data wherein the factors involved in the research included ‘Global Competitive Threats’,’ Global Market Opportunities’, and ‘Global Market Uncertainty’ for Globalisation and ‘firm performance’. The results of the research revealed that there exist a significant relationship between the variables of globalisation and firm performance. Furthermore, the researcher has also provided recommendations for the UK IT industry to stay competitive.